The benefits of male ejaculate sex peptide transfer in Drosophila melanogaster. - Fricke, C; Wigby, S; Hobbs, R; Chapman, T (2009)
The accessory gland protein (Acp) ejaculate molecules of male Drosophila melanogaster mediate sexual selection and sexual conflict at the molecular level. However, to date no studies have comprehensively measured the timing and magnitude of fitness benefits to males of transferring specific Acps. This is an important omission because without this information it is not possible to fully understand the strength and form of selection acting on adaptations such as Acps. Here, we measured the fitness benefits to males of ejaculate sex peptide (SP) transfer. SP is of interest because it is a candidate for mediating sexual conflict: its frequent receipt reduces female fitness. In single matings with virgin females SP is known to increase egg laying and decrease receptivity. Hence, we predicted that SP could: (i) boost a male's absolute paternity by increasing offspring production and delaying female remating and/or (ii) boost relative paternity share. We tested these predictions using two different lines of SP-lacking males, in both two-mating and free-mating assay conditions. SP transfer conferred higher absolute, but not relative, male reproductive success. In matings with virgin females, SP transfer increased mating productivity and delayed remating and hence the onset of sperm competition. In already mated females, SP transfer did not elevate absolute progeny production, but did increase intermating intervals and hence the period over which a male could gain paternity. Consistent with this, under free-mating conditions over an extended period, we detected a 'per-mating' fitness benefit for males transferring SP. These benefits are consistent with a role for SP in mediating conflict, with SP acting to maximize short-term fitness benefits for males.